2011
DOI: 10.1186/1748-7161-6-23
|View full text |Cite
|
Sign up to set email alerts
|

School screening and point prevalence of adolescent idiopathic scoliosis in 4000 Norwegian children aged 12 years

Abstract: BackgroundSchool screening for adolescent idiopathic scoliosis (AIS) is discussed. The aim of the present study was to describe the point prevalence of AIS and to evaluate the effectiveness of school screening in 12-year- old children.MethodsCommunity nurses and physical therapists in the Southern Health region of Norway including about 12000 school children aged 12 years were invited to participate. All participating community nurses and physical therapists fulfilled an educational course to improve their kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 35 publications
(47 reference statements)
1
53
0
12
Order By: Relevance
“…13 Among the 1000 school children whose angle of trunk rotation (ATR) was measured, 7 (0.7%) and 10 (1%) had a reading >7 o in the Scoliometer device and App respectively. In this study, it was found that gender did not have any statistically significant association with positive scoliosis findings.…”
Section: Scoliometer Device and Scoliometer Appmentioning
confidence: 99%
“…13 Among the 1000 school children whose angle of trunk rotation (ATR) was measured, 7 (0.7%) and 10 (1%) had a reading >7 o in the Scoliometer device and App respectively. In this study, it was found that gender did not have any statistically significant association with positive scoliosis findings.…”
Section: Scoliometer Device and Scoliometer Appmentioning
confidence: 99%
“…Scoliometer was used to measure any hump detected during Adams forward bending test. 41,44 Abnormalities involving the trunk or spine (shoulder asymmetry, scapular prominence, pelvic/hip prominence, space between arm and body, head center over the pelvis, any tell tale sign of spinal disease) were recorded. The children with positive forward bending test and scoliometer angle of 5 degrees or more were sent for the radiographic evaluation at the nearby hospital.…”
Section: Methodsmentioning
confidence: 99%
“…6,7,8,9 Screening at school for the early detection of scoliosis has been introduced and being practiced in many countries. [10][11][12][13][14][15][16][17][18][19][20][21][33][34][35][36][37][38][39][40] Previous studies have both encouraged 7,8,31,33,37,41 and discouraged routine screening. Opponents to scoliosis screening have focused on concerns about a low predictive value of screening, and the cost effectiveness of referral.…”
Section: Introductionmentioning
confidence: 99%
“…The FBT was always used, and a specially trained nurse assisted in the screening. Sweden is the only Scandinavian country with an ongoing SSS [2,34] .…”
Section: Status Of Sss In the Worldmentioning
confidence: 99%
“…After the Moiré topography was introduced, it revealed twice as many cases of scoliosis as did conventional clinical screening, despite many false positive results [36] . However, no specific SSS programs have been successfully implicated [34] .…”
Section: Status Of Sss In the Worldmentioning
confidence: 99%